Prophetic Leadership Communication Manajer dalam Membangun Kerja Sama Tim Sepak Bola Kacipo FC di Sebatik Tengah, Kabupaten Nunukan, Kalimantan Utara - Maris Mardin; Twediana Budi Hapsari (STIKes Ibnu Sina Ajibarang, 2025)
Leadership communication plays an important role in building interpersonal relationships and teamwork, particularly in sports organizations. One approach that can be applied is Prophetic Leadership Communication, which is based on the values of shiddiq, amanah, tabligh, and fathanah. This study aims to describe the implementation of Prophetic Leadership Communication by the manager in building interpersonal relationships and strengthening teamwork in Kacipo FC Football Team, Sebatik Tengah, Nunukan Regency, North Kalimantan. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving the manager and players of Kacipo FC. The data were analyzed using data reduction, data display, and conclusion drawing. The findings indicate that the manager has implemented the values of Prophetic Leadership Communication through honest, responsible, open, and intelligent communication. These values contribute to building interpersonal trust, strengthening players' commitment and loyalty, and improving teamwork. Therefore, Prophetic Leadership Communication serves as an effective leadership communication approach in strengthening teamwork within Kacipo FC.